The impact of accounting software on accountants’ ‎performance ‎in the furniture companies who are based in ‎Erbil city: A field ‎study.‎ - Agha , Dilshad A.; Abdulla , Dr.Arshad S.; Nanakali, Susan O. Othman (Polytechnic Journal of Humanities and Social Sciences, 2024)
Abstract— Furniture companies in the city of Erbil served as the ‎focus of this study, ‎which set out to examine the effect ‎of accounting software on accountants’ ‎performance. ‎The goal was to consider the performance of ‎accountants as the ‎accounting system was being ‎developed, by looking at its impact on their ‎performance ‎in terms of skills, knowledge and creativity. The ‎outcomes from ‎this study’s statistical analyses, which ‎were used to evaluate the hypotheses, ‎are shown in the ‎tables below. The results show that recent improvements ‎to ‎accounting systems in general, and accounting ‎software in particular, can ‎enhance performance. The ‎results of the hypothesis test, which showed a ‎‎substantial association between the independent variable ‎of accounting ‎software and each of the dependent ‎variables—skills, knowledge, and ‎creativity—support ‎this. The outcomes of the statistical analysis have ‎‎established acceptable results.‎ Keywords— Accounting ‎software, Accountants, ‎performance, skills, ‎knowledge, ‎innovation. ‎